Synthesis and Crystal Structure of a Thiosemicarbazone - Li, Peiyuan; Su, Wei; Lu, Chengsheng; Liu, Lifeng; Zhou, Quan; Qian, Quanquan (Asian Journal of Chemistry, 2013)
A thiosemicarbazone single crystal synthesized with molecular formula as C14H12N4S, was synthesized by 3-phthalaldehyde and 4-methylthiosemicarbazide. The crystal is monoclinic, space group Pc with unit cell parameters: a = 11.3218(12) Å, b = 7.0361(5) Å, c = 8.5416(6) Å, a = 90.00º, b = 103.821(9)º, g = 90.00º, V = 660.74(10)Å3, Z = 2, Mr = 268.34, Dc = 1.349 g/cm3, μ = 0.236 mm-1, F(000) = 280, R = 0.0390, wR = 0.1016 for 2130 reflections with I > 2s(I).